Cambiamenti della biodiversità nel benthos sessile del porto di Genova su scala pluridecennale - Abate, Alessandro; Bavestrello, Giorgio; Bianchi, Carlo Nike; Canessa, Martina; Garaventa, Francesca; Enrichetti, Francesco; Faimali, Marco; Morri, Carla; Piazza, Veronica; Ridella , Beatrice (Biologia Marina Mediterranea, 2025)
Fifty years after pioneer studies, the fouling of the Genoa harbour was studied again with similar methodologies. Panels immersed at 1 m depth were collected and analysed monthly to assess biodiversity, biomass, and community dynamics. The preliminary results showed the persistence of key species like Amphibalanus amphitrite, Hydroides elegans, and Schizoporella errata. However, Hydroides dirampha, a tropical species, has increased, possibly due to rising sea temperatures. Simplaria pseudomilitaris was once the only abundant spirorbid species on the panels, present only in the winter and spring months; today, also Neodexiospira pseudocorrugata shows a comparable abundance, and both species also appear in mid-summer. Some once-abundant organisms, such as the calcareous sponge Sycon ciliatum, the hydroid Ectopleura crocea, and the ascidian Ciona intestinalis, have now disappeared. The changes observed may represent the effect of the sea water warming recorded in the last decades.